IMPACT OF RAPID ANTIGEN DETECTION TESTS IN THE DIAGNOSIS OF STREPTOCOCCAL TONSILLOPHARYNGITIS IN CHILDREN (Iraqi Journal of Medical Sciences, 2017)
Background: Tonsillopharyngitis among children considered as a major public health problem in the community, because of post-streptococcal complications, cost, time consuming diagnostic tests and un-necessary antibiotics. Objective: To determine the validity of Rapid Antigen Detection Test (RADT) in the diagnosis of streptococcal tonsillopharyngitis in comparison with clinical and bacterial culture method.Methods: Throat swabs were taken from 214 children with tonsillopharyngitis in Baghdad from 20th November 2015 to 30th May 2016. Tonsillopharyngitis diagnosed by clinical, culture on blood agar and RADT.Results: S. pyogenes were recovered from 116 (54.2%) cases. S. pyogenes infection alone or with overgrowth of other bacteria is associated with recommendation for tonsillectomy, and indices for MCIsaac clinical prediction for Streptococcal pharyngitis. RADT detection of S. pyogenes revealed 83.62% sensitivity and 95.92% specificity. MCIsaac clinical prediction 89.66% sensitivity and 44.9% specificity. The combined MCIsaac-RADT algorithm had increased sensitivity with an increased point of score and specificity found to be inversely associated with points of score.Conclusion: For routine work, this study supports clinical screening with MCIsaac score for all children with tonsillopharyngitis and subsequent testing by Strep A RADT to facilitate the decision for antibiotic use.Keywords: Rapid antigen detection, streptococcus pyogenes, tonsillopharyngitisCitation: Hadi ZH, Ghazi HF, Abdulla MM. Impact of rapid antigen detection tests in the diagnosis of streptococcal tonsillopharyngitis in children. Iraqi JMS. 2017; Vol. 15(3): 305-313. doi: 10.22578/IJMS.15.3.13
Keywords: Rapid antigen detection; streptococcus pyogenes; tonsillopharyngitis